Rethinking Social Context in Technological Responsibility - Steven Umbrello, Technology Ethics: Responsible Innovation and Design Strategies - Ayat Mirzaie (Academicus International Scientific Journal)

(untitled)
This review explores Steven Umbrello’s work on Technology Ethics, an interdisciplinary examination of the complex relationship between technology and society. The book critically examines foundational concepts such as technological instrumentalism, determinism, social construction, and interactional perspectives, highlighting the dynamic interplay between values, design, and ethics. Umbrello’s advocacy for value-sensitive design and responsible innovation as practical frameworks for addressing emerging challenges, including AI and sociotechnical systems, is a key takeaway. While the book provides a solid foundation, it raises further unresolved questions about agency in increasingly autonomous technologies and the methodological challenges associated with empirically studying interactional perspectives. This review underscores the book’s practical value for scholars, practitioners, and policymakers grappling with technological innovations’ ethical and societal implications.